2021
DOI: 10.3390/ijms22031282
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and Divergence of Sugar and Cytokinin Signaling in Plant Development

Abstract: Plants adjust their growth and development through a sophisticated regulatory system integrating endogenous and exogenous cues. Many of them rely on intricate crosstalk between nutrients and hormones, an effective way of coupling nutritional and developmental information and ensuring plant survival. Sugars in their different forms such as sucrose, glucose, fructose and trehalose-6-P and the hormone family of cytokinins (CKs) are major regulators of the shoot and root functioning throughout the plant life cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 243 publications
(294 reference statements)
1
31
0
1
Order By: Relevance
“…Meanwhile, our results also showed that sucrose and hormones were necessary for the physiological differentiation of floral buds. Previous studies have highlighted that sucrose-mediated signaling is interconnected with hormone-mediated floral induction, possibly as an additional part of flowering initiation (Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, our results also showed that sucrose and hormones were necessary for the physiological differentiation of floral buds. Previous studies have highlighted that sucrose-mediated signaling is interconnected with hormone-mediated floral induction, possibly as an additional part of flowering initiation (Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sugars and CKs play pivotal roles in plant morphogenesis and development during both the vegetative and reproductive stages of plant life [ 19 ]. There are two types of CKs: adenine-type CKs, including kinetin, zeatin and 6-benzylaminopurine (BA), and phenylurea-type CKs, represented by diphenylurea and thidiazuron.…”
Section: Discussionmentioning
confidence: 99%
“…The fine-tuned interactions between nutrients and hormones play pivotal roles in orchestrating plant yield and resistance to abiotic and biotic constraints [ 18 , 19 ]. Sugars and cytokinins (CKs) are among the most central regulators during plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) hexokinase (HXK)-sensing system, (2) hexose transport-associated sensor (SUCROSE-NONFERMENTATION1-RELATED PROTEIN KINASE1 (SnRK1) and TARGET OF RA-PAMYCIN (TOR) kinase) and ( 3) the Suc-specific pathway, which may implicate a signaling Suc transporter [120]. Germination, hypocotyl elongation, flowering, senescence, root and leaf growth, metabolism of carbon and nitrogen, pathogen attack and wounding are some of the processes that are shown to be influenced by glucose signaling via hexokinasedependent pathways [121].…”
Section: Sucrose Interferes With Auxin and Cytokinin Signaling In The Regulation Of Shoot Organogenesismentioning
confidence: 99%